ANALISIS PENGARUH KEBIJAKAN HUTANG, KEBIJAKAN DIVIDEN, DAN PERTUMBUHAN PERUSAHAAN TERHADAP NILAI PERUSAHAAN DENGAN PROFITABILITAS SEBAGAI VARIABEL INTERVENING PADA PERUSAHAAN PEMBIAYAAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Sinaga, Febriani Florentin (Jurusan Manajemen Fakultas Ekonomi dan Bisnis, 2019)
This study aims to analyze the effect of debt policy, dividend policy, and company growth on company value, with profitability as the intervening variable, in the finance companies listed on the Indonesia Stock Exchange (IDX). The population of this study was all finance companies listed on IDX for the period of 2015 and 2016. The purposive sampling method was used in this study with the sample consisted of 12 finance companies. Data used were financial data sourced from the website of IDX. Data were analyzed using path analysis with two equations, i.e., the factors affecting company value and the factors affecting company profitability. Results of the study showed that debt policy, dividend policy, company growth, and profitability have no significant effect on company value. This study also found that debt policy and company growth have no significant effect on profitability, while dividend policy significantly affects profitability. Keywords : Debt policy, dividend policy, company growth, profitability